The Impact of Religious Beliefs and Practices on Coping with Health Challenges Posed by Covid-19 - Anastasiadou, Penelope; Tsironis, Christos; Cheristanidis, Stavros; Andreadis, Dimitrios; Poulopoulos, Athanasios (European Scientific Journal, ESJ, 2023)
In the midst of the Covid-19 pandemic, the aim of the present study was to investigate to what extent the undergraduate students of the Department of Dentistry, Aristotle University of Thessaloniki, felt the need to come closer to their own religiosity, spirituality, or faith. Materials and methods: Empirical research was conducted by means of an anonymous questionnaire, comprising demographics and items focusing on religiosity, spirituality, and faith. The survey results were processed using â€œMICROSOFT EXCEL IBM SPSS STATISTICS 24â€ statistical processing software. Results: To overcome health dilemmas, the wide majority of students did not focus on religious & spiritual practices (70% & 66.7%) while at the same time, their religiosity & spirituality was not enhanced (74% & 78%). However, for the same period, 53% of the students stated that their faith was enhanced. Conclusions: While overall studentsâ€™ religiosity & spirituality indicators were low, for the same period they stated that their faith in overcoming health distress was strengthened, which triggers new questions and prompts further research in the field of humanities.